Analysis of single-cell RNA sequencing in human oocytes with diminished ovarian reserve uncovers mitochondrial dysregulation and translation deficiency - Xin Li; Xingwu Wu; Hui Zhang; Peipei Liu; Leizhen Xia; Nana Zhang; Lifeng Tian; Zengming Li; Jing Lu; Yan Zhao; Jun Tan (BMC, 2024)
Abstract Background Diminished ovarian reserve (DOR) is clinically characterized by a decrease in the number of available ovarian follicles and a decline in the quality of oocytes, accompanied by hormonal changes. Low quality of DOR oocyte leads to impaired embryo development, an increased risk of aneuploid pregnancies and miscarriages. However, the specific pathogenic mechanism remains unclear, posing a significant challenge for assisted reproductive technology. Methods For the first time, our study employed single-cell RNA sequencing to reveal the altered transcriptomic landscape of DOR oocytes at GV stage after ovarian stimulation. Differentially expressed genes analysis (DEGs), functional enrichment analysis, weighted gene co-expression network analysis (WGCNA) and protein-protein interactions network analysis were performed. Results We found 132 up-regulated genes and 466 down-regulated genes in DOR oocytes, with the down-regulated genes primarily enriched in mitochondrial function and translation. Hub genes, identified through integrated analysis of WGCNA and DEGs, were further validated in DOR and control oocytes using RT-qPCR. By utilizing hub genes and employing transcription factor enrichment tools, it had been predicted that pleomorphic adenoma gene 1 (PLAG1) played a crucial role as a transcriptional regulatory factor in DOR oocytes. Additionally, we conformed the PLAG1-IGF2 axis was dysregulated in DOR oocytes. Conclusions Transcriptome analysis revealed that DOR oocytes exhibited mitochondrial dysfunction and translational defects, and the PLAG1-IGF2 axis might be a potential contributor for the low quality of DOR oocytes.